Síntese da zeólita analcima por meio do processo hidrotermal e empregando o resíduo de caulim como fonte de silício e alumínio - SANTOS, Márjorye Katharine Aires dos (2019)
The kaolin mining industry is of great socioeconomic importance for Brazil. In spite of this fact, it should be noted that in the beneficiation process of this ore, environmental and economic consequences are generated, mainly due to the residual storage. In order to contribute to the solution of this problem, this research consists in developing an optimized process for the synthesis of the Analcima zeolite from the kaolin residue. The methods used in this study were based on the experimental methodology, starting with the treatment of the residue that took place in the greenhouse for 4 hours at 100 ℃. Then, the material was calcined generating four samples of metacaulinite, which together with sodium metasilicate and sodium hydroxide formed the mixtures for the first series of experiments. In this series, each sample was synthesized for eight hours at 150 ℃. After conducting them to the X-ray Diffractometer (XRD), optimized parameters were selected and the study followed the second experimental part, in which only the reaction time varied. With the results of characterization in XRD and Scanning Electron Microscopy (SEM), the optimum production of Analcima was found to be the best form.